2017
DOI: 10.15547/ast.2017.03.044
|View full text |Cite
|
Sign up to set email alerts
|

Avifauna abundance and diversity in Jos wildlife park, Nigeria

Abstract: Editors and Sections Genetics and Breeding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…While in the evening, a total of 988 birds comprising of both terrestrial and aquatic birds were recorded. This is similar to the findings of Kwaga et al 5 , It was observed that terrestrial birds were higher in number (11 individuals) than water birds (6 individuals). In Table 4, cattle egret (Ardeola ibis), had the highest relative frequency (21.55%) followed by Vinaceous dove (Streptopelia decipiens) 13.73%.…”
Section: Resultssupporting
confidence: 92%
“…While in the evening, a total of 988 birds comprising of both terrestrial and aquatic birds were recorded. This is similar to the findings of Kwaga et al 5 , It was observed that terrestrial birds were higher in number (11 individuals) than water birds (6 individuals). In Table 4, cattle egret (Ardeola ibis), had the highest relative frequency (21.55%) followed by Vinaceous dove (Streptopelia decipiens) 13.73%.…”
Section: Resultssupporting
confidence: 92%
“…Khobe and Kwaga (2017) in their studies on birds' species of Jos Wildlife Park, Nigeria reported that the level of distribution of bird species in a habitat is normally as a result of an occurrence of plant species that support their population and to variation in species specification requirements in the choice of habitat. This finding is also in agreement with Kwaga et al (2017) that the distribution of birds' species is largely dependent on the availability of food, water and cover. In contrast to my findings of higher relative abundance of birds of prey, Takele and Afework (2018) recorded Wattled Ibis (B. carunculata).…”
Section: Relative Abundance Of Birds Of Prey In Baturiya Wetlandssupporting
confidence: 92%
“…Khobe and Kwaga (2017) in their studies on birds species of Jos Wildlife park, Nigeria reported that the level of distribution of bird species in a habitat is normally as a result of an occurrence of plant species that support their population and to variation in species specification requirements in the choice of habitat. This finding is also in agreement with Kwaga et al, (2017) that the distribution of birds' species is largely dependent on the availability of food, water and cover.…”
Section: Relative Abundance Of Birds Of Prey In Baturiya Wetlandssupporting
confidence: 92%